Agonistic participation: A political and architectural opportunity. (1st December 2013) - Beyerle, Ammon
This study explores theory and practice in architecture and participation through an ethnographic exposition of an architectural design and community development process for Hub Melbourne, a new coworking space in Melbourne. As well as contributing a practical example of a participatory process in architecture, the analysis aims to situate learnings from the architectural practice here studio in a long history of participation in architecture. Claire Bishop's 'The social turn: Collaboration and its discontents' (2006) is used as a starting point from which to argue for autonomous evaluations in social practice that value the production of ethical and political engagement as creative content. This content is intricately connected to the project's aesthetics. Borrowing from the pluralist political theory of Chantal Mouffe, the article suggests that participation is difficult in architecture, yet presents opportunities if conflict between stakeholders is valued in an agonistic way.